Analysis Of Bumdes Management Success (Qualitative Descriptive Study Of Successful Analysis Of Bumdes Management In Indonesia Through Online News Sites) - Evi Puspita; Rini Nurbayanti; Dea Nurmastin Novianti (Jurnal Ilmu Sosial Politik dan Humaniora (Jisora), 2022)
The success of BUMDes management is widely loaded on social media, if viewed from one of the functions of social media itself that is a means used to disseminate and convey information. BUMDes is an economic pillar in the village that functions as a social institution (social institution) and commercial (commercial institution). The main objective of BUMDes is to improve the welfare of rural communities. The purpose of this study is to see the point of spread of the success of BUMDes management in Indonesia and present information on the success of BUMDes management. The researchers use the theory of Marry Paker Follet in Syamsuddin (2017: 64) put forward the notion of management. The method used by researchers is a qualitative descriptive method through data collection techniques such as interviews, observation and analysis. Involving members of the Garut BUMDes Association forum, Garut University Lecturer and Head of the Garut Regency DPMD Economic and Village Development Section. The results of data collection conducted by researchers online through news sites on the internet that there are about 45,549 BUMDes formed in Indonesia, some villages have not been successful yet this has led to the failure of BUMDes, the first mistake choosing a haphazard business idea, the second failing in accessing resources or village potential, thirdly making wrong decisions ineffective, and fourthly not being able to manage the business well. However, a small number of villages in the territory of Indonesia have been able to manage BUMDes well so that not only can be said to be a program success but also able to produce a wider positive impact. In order to be able to move into a key driving force for the prosperity of rural communities, there are three successes, namely changing the mindset, perseverance, and control.